Taking care of your rabbit - Piers, Helen; Vriends, Matthew M., 1937- (Hauppauge, NY : Barron's, 1992)
Offers advice on selecting, feeding, housing, and maintaining the health of a pet rabbit.
Includes bibliographical references (p. 31) and index.
Keywords: Rabbits -- Juvenile literature